Theoretical Review of Evaluation of the Potential for Collapse of las dunitas (the Dunites) of Medellín - Rodríguez, Óscar Egidio; Salgado, Eileen Carolina; Gallo, Adriana Maria; Vanegas, Eduardo Danilo (Ingeniería Solidaria, 2014)
This article refers to the first stage of research framed by a bibliographic and theoretical review of all criteria, methods and tests that have been used to determine the degree of collapsibility of soils. A second stage will consist of the application of a series of laboratory tests to obtain the relevant conclusions in order to identify the degree of soil collapse. This research is being carried out in the city of Medellín, mainly in the eastern zone where la dunita (the dunite) is located. The idea arose from a series of events in this sector over the years that have affected some of the main roads, such as the Medellín-Bogotá highway, which connects Medellín to the capital of Colombia, and the Las Palmas highway connecting Medellín to José María Córdoba international airport.
Keywords: dune; degree of collapsibility; tests; catastrophic events